2022
DOI: 10.21203/rs.3.rs-1759950/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification of MATE family, and functional analysis of MATE involved in anthocyanin accumulation in Daucus carota

Abstract: Multidrug and toxic compound extrusion (MATE) is a family of membrane transporters that transport ions and secondary metabolites like anthocyanins in plants. Although various research on MATE has been carried out on different plant species, this is the first comprehensive report to exploit the Daucus carota genome to identify the MATE gene family. We investigated the chromosomal distribution, gene duplication, motif identification, cis-element analysis, in vitro cultures, stress treatment, protein docking, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous research used molecular docking to show that the five amino acid residues of PrMATE1 may bind to PA (Morales‐Quintana et al, 2019). Moreover, molecular dynamics simulations have revealed that 10 key amino acids of DcMATE21 bind to anthocyanins (Saad et al, 2023). These results indicate that the amino acids of DTX/MATE binding to substrates may vary with the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research used molecular docking to show that the five amino acid residues of PrMATE1 may bind to PA (Morales‐Quintana et al, 2019). Moreover, molecular dynamics simulations have revealed that 10 key amino acids of DcMATE21 bind to anthocyanins (Saad et al, 2023). These results indicate that the amino acids of DTX/MATE binding to substrates may vary with the species.…”
Section: Discussionmentioning
confidence: 99%
“…Under the process of evolution, DTX/ MATE transporters have expanded considerably in plants, resulting in large gene families in different species (Upadhyay et al, 2019). To date, 45 DTX/MATE genes have been identified in rice (Wang et al, 2016), 70 in Medicago truncatula (Wang et al, 2017), 72 in cotton (Xu et al, 2019), 65 in persimmon (Zhu et al, 2019), and 45 in Daucus carota (Saad et al, 2023).…”
Section: Introductionmentioning
confidence: 99%